Role of Epigenetics in Modulating Phenotypic Plasticity against Abiotic Stresses in Plants - Fayaz Ahmad Dar; Naveed Ul Mushtaq; Seerat Saleem; Reiaz Ul Rehman; Tanvir Ul Hassan Dar; Khalid Rehman Hakeem (International Journal of Genomics)
Plants being sessile are always exposed to various environmental stresses, and to overcome these stresses, modifications at the epigenetic level can prove vital for their long-term survival. Epigenomics refers to the large-scale study of epigenetic marks on the genome, which include covalent modifications of histone tails (acetylation, methylation, phosphorylation, ubiquitination, and the small RNA machinery). Studies based on epigenetics have evolved over the years especially in understanding the mechanisms at transcriptional and posttranscriptional levels in plants against various environmental stimuli. Epigenomic changes in plants through induced methylation of specific genes that lead to changes in their expression can help to overcome various stress conditions. Recent studies suggested that epigenomics has a significant potential for crop improvement in plants. By the induction and modulation of various cellular processes like DNA methylation, histone modification, and biogenesis of noncoding RNAs, the plant genome can be activated which can help in achieving a quicker response against various plant stresses. Epigenetic modifications in plants allow them to adjust under varied environmental stresses by modulating their phenotypic plasticity and at the same time ensure the quality and yield of crops. The plasticity of the epigenome helps to adapt the plants during pre- and postdevelopmental processes. The variation in DNA methylation in different organisms exhibits variable phenotypic responses. The epigenetic changes also occur sequentially in the genome. Various studies indicated that environmentally stimulated epimutations produce variable responses especially in differentially methylated regions (DMR) that play a major role in the management of stress conditions in plants. Besides, it has been observed that environmental stresses cause specific changes in the epigenome that are closely associated with phenotypic modifications. However, the relationship between epigenetic modifications and phenotypic plasticity is still debatable. In this review, we will be discussing the role of various factors that allow epigenetic changes to modulate phenotypic plasticity against various abiotic stress in plants.